Fulfillment challenges in online marketplaces : a qualitative study on Finnish sellers integrated with Amazon and Tmall - Zare, Razieh (My University, 2021)
Joining the marketplace as a Business-to-Consumer (B2C) sales channel has become increasingly popular among companies, especially during the pandemic 2020. However, joining the marketplace has not been straightforward for companies since it requires some internal changes, understanding the marketplace requirements thoroughly, and the fulfillment process. This study aims to understand the fulfillment models and Finnish companies' fulfillment challenges in the online marketplaces. The theoretical background of this study consists of several concepts that are connected to the research topic. These include the fulfillment model, fulfillment challenges, and the role of logistics partners in order fulfillment. This study employs a qualitative research method, namely secondary data from Amazon and Tmall websites and interviewing Finnish companies integrated with Amazon and Tmall, Posti Oy as a logistics service provider, and one Finnish Amazon agency as marketplace expert. The results indicate that the Finnish companies that joined marketplaces faced external and internal challenges. One of the main internal challenges is resource reallocation in the company. External challenges include selecting fulfillment models, creating transportation and distribution links, understanding marketplace fulfillment and delivery requirements. The key new learning from my research is that following the marketplace regulations and requirements is essential to survive and compete in online marketplaces. Another key learning is that the proper selection of the fulfillment model is critical. Factors affecting the choice of fulfillment models are item size and price, level of novelty, and sales volume in marketplaces. Moreover, logistics partners play a crucial role in the marketplace fulfillment process. In selecting logistics partners, sellers look for value propositions like speed, accuracy, price, easy integration, and a good set of networks and services.
Keywords: fulfillment process, fulfillment challenges, online marketplace, logistics partners